Implementation of Outdoor Learning with Qr Code-Based Treasure Map Thinking Media to Improve Critical Thinking of Students in Social Studies Lessons - Lala Zaenia Pratiwi; Nurul Ratnawati (STKIP Taman Siswa Bima, 2025)
This study aims to describe the implementation of Outdoor Learning with QR Code-based Treasure Map Thinking media in improving critical thinking of students in social studies subjects of class VIII C at SMP Negeri 16 Malang. This study uses a mixed method approach with the type of Classroom Action Research (CAR) with the Kemmis and Mc Taggart models, which are implemented in two cycles. Data collection techniques in this study are structured observation, documentation and structured interviews. Data analysis techniques are descriptive statistics and data reduction. The results of the study showed a significant increase in students' critical thinking skills, as shown by the results of the pre-cycle, cycle 1 and cycle 2 as well as direct observation in the field. After the QR Code-based Treasure Map Thinking media was proven to be able to improve the critical thinking skills of class VIII C students which can be proven from the results of cycle 1 and cycle 2 which experienced a significant increase this media can be said to be effective and can be used as an alternative media for other teachers who teach social studies subjects. The implementation of the Outdoor Learning model with QR Code-based Treasure Map Thinking media systematically through the pre-cycle, cycle I, and cycle II stages has proven effective in improving students' critical thinking skills. This is indicated by a significant increase from an average of 36.71% in the pre-cycle to 86.29% in cycle II